Optical Imaging of PARP1 in Response to Radiation in Oral Squamous Cell Carcinoma. - Susanne Kossatz; Wolfgang A Weber; Thomas Reiner (PLoS ONE, 2016)
Targeting and inhibiting DNA repair pathways is a powerful strategy of controlling malignant growth. One such strategy includes the inhibition of PARP1, a central element in the intracellular DNA damage response. To determine and visualize the expression and intercellular distribution of PARP1 in vivo, and to monitor the pharmacokinetics of PARP1 targeted therapeutics, fluorescent small probes were developed. To date, however, it is unclear how these probes behave in a more realistic clinical setting, where DNA damage has been induced through one or more prior lines of therapy. Here, we use one such imaging agent, PARPi-FL, in tissues both with and without prior DNA damage, and investigate its value as a probe for PARP1 imaging. We show that PARP1 expression in oral cancer is high, and that the uptake of PARPi-FL is selective, irrespective of whether cells were exposed to irradiation or not. We also show that PARPi-FL uptake increases in response to DNA damage, and that this increase is reflected in higher enzyme expression. Our findings provide a framework for measuring exposure of cells to external beam radiation, and could help to elucidate the effects of such treatments non-invasively in mouse models of cancer.